Petrophystics and Nannobiostratigraphy data from the Coniacian-Santonian interval of the Kometan Formation in the Bai Hassan-86 Oil Field, Northern Iraq: Implication for the Oceanic Anoxic Event - Alhialy, Rana Abdulelah; Al-Badrani, Omar Ahmed; Malak, Zaid Abdulwahab (Iraqi Journal of Science, 2025)
The late Turonian to early Campanian Kometan Formation is widespread in northern and central Iraq. The study section is located in Northern Iraq, northwest Kirkuk. This formation is composed primarily of limestone, dolomitic limestone, and black shale, with nodules of chert distributed throughout the formation. The lower contact of the formation with the Gulneri with the Mushorah Formations is unconformable. The current study used 80 thin sections that showed the presence of planktonic foraminifera and 55 samples. The black shale beds in the middle formation were determined through the Gamma log. And also five nannobiozones identified, they are Eiffellithus eximius Interval Zone (CC12) Marthasterites furcatus Interval Zone (CC13), Micula staurophora Interval Zone (CC14), Reinhardites anthophorus Interval Zone (CC15), Lucianorhabdus cayeuxii Interval Zone (CC16). Depending on planktonic foraminifera and the biostratigraphy of calcareous nannofossils, evidence of Bai Hassan-86 well determined the age of the Oceanic Anoxic Event (OAE3) was recorded in Upper Turonian – lower Santonian.